المهارات العقلية المتضمنة في كتاب الرياضيات للصف الثاني المتوسط في ضوء ضوء أنموذج مارزانو - أحمد، رسول رشيد; مشكور، غالب خزعل محمد (الجامعة المستنصرية - كلية التربية الأساسية, 2022)
يهدف البحث الحالي للتعرف على تضمين المهارات العقلية في محتوى كتاب الرياضيات للصف الثاني المتوسط ضمن انموذج مارزانو في جمهورية العراق للعام الدراسي 2021)/ 2022)م من خلال الإجابة عن سؤال البحث: السؤال الأول: ما نسبة تضمين المهارات العقلية في كتاب الرياضيات للصف الثاني المتوسط؟ اعتمد الباحث المنهج الوصفي التحليلي، وذلك لملائمته هدف البحث إذ تكونت عينة البحث الحالي من المادة العلمية في كتاب الرياضيات المقرر للصف الثاني المتوسط وتم اعتماد وحدة الفكرة التي قد تكون صريحة أو ضمنية كوحدة للتسجيل والتكرار كوحدة للعد، ولتحقيق هدف البحث أعد الباحث قائمه أولية بــــ (المهارات العقلية الرئيسة والفرعية منها) بعد اطلاعه على الأدبيات والدراسات التي تناولت تحليل محتوى الكتب المدرسية وفقا للمهارات العقلية. ثم عرضت هذه القائمة بصيغتها الأولية على عدد من السادة المحكمين من ذوي الخبرة والاختصاص حيث حصلت القائمة على اتفاق أكثر من (93%) من آراء المحكمين. وتم تحليل محتوى كتاب الرياضيات للصف الثاني المتوسط وفقا للمهارات العقلية الرئيسة والفرعية منها. وتم عرض انموذجا من عينة التحليل على عدد من السادة المحكمين من ذوي الخبرة والاختصاص وقد اتفقوا على صلاح عملية التحليل، وجاء التأكد من ثبات عملية التحليل بطريقتين الأولى الباحث مع نفسه والثانية الباحث مع محلل آخر بعد مضي فترة زمنيه محدده (أربعة أسابيع) وحصلت على نسبة أتفاق تراوحت بين (89%- 91%) أذ تمت معالجة البيانات ونسب الثبات باستخدام معادلة هولستي (Holsti). وتم التوصل إلى النتائج الآتية: حصول كتاب الرياضيات للصف الثاني المتوسط على التكرارات للمهارات العقلية إذ حصل على 785)) تكرارا وبنسبه مئوية (100%) أما بالنسبة للمهارات الرئيسة: حيث جاءت فئة مهارات التنظيم بالمرتبة الأولى في الكتب كافة بعد أن حصلت على) 319) تكرارا وبنسبة (40.6%). تليها فئة مهارات التحليل بالمرتبة الثانية بعد أن حصلت على (110) تكرارا وبنسبة (14%). ثم جاءت بقية الفئات بنسب متفاوتة. أما بالنسبة للمهارات الفرعية: فقد جاءت مهارة الترتيب بالمرتبة الأولى للكتب الثلاثة على (175) تكرارا وبنسبة (22%). تليها مهارة التمثيل بالمرتبة الثانية بعد أن جمعت (82) تكرارا وبنسبة (10%). وجاءت المهارات الفرعية الأخرى بنسب متفاوتة في الاهتمام من الكتاب المقرر بينما أهملت مهارتي صياغة الأسئلة ومهارة تحديد الأفكار الرئيسة. وفي ضوء ذلك أوصى الباحث بضرورة التوازن في نسب تضمين المهارات العقلية في كتاب الرياضيات للصف الثاني المتوسط وخرج بعدد من التوصيات والمقترحات. This current university research presents the educational inclusion in the content of the mathematics book for the second intermediate grade within the Marzano model in the Republic of Iraq for the year 2021) / 2022 AD. By answering the research question: The first question: What is the percentage of including mental skills in the mathematics book for the second intermediate grade? The researcher adopted the descriptive-analytical approach, in order to suit the goal of the research, as the current research sample consisted of the scientific material in the mathematics textbook for the second intermediate grade, and the idea unit was adopted Which may be explicit or implicit as a unit for recording and repetition as a unit for counting, and to achieve the goal of the research, the researcher prepared an initial list of (main and sub mental skills) after reviewing the literature and studies that dealt with analyzing the content of textbooks according to mental skills. Then this list was presented in its initial form to a number of arbitrators with expertise and competence, where the list obtained agreement on more than (93%) of the arbitrators' opinions. The content of the mathematics book for the second intermediate grade was analyzed according to the main and sub mental skills. A sample of the analysis sample was presented to a number of arbitrators with expertise and competence and they agreed on the validity of the analysis process, and the confirmation of the stability of the analysis process came in two ways: the first is the researcher with himself and the second is the researcher with another analyst after a specified period of time (four weeks) and I got The percentage of agreement ranged between (89%- 91%), as the data were processed and the reliability rates were used using the Holsti equation. The following results were obtained: The mathematics book for the second intermediate grade obtained the repetitions of mental skills, as it obtained 785) recurrences with a percentage of (100%) . As for the main skills: Where the category of organization skills ranked first in all books after it obtained (319) recurrences, at a rate of (40.6%). It is followed by the category of analysis skills in the second place, after it got (110) recurrences and at a rate of (14%). Then came the rest of the categories in varying proportions. As for the sub-skills: The skill of arranging ranked first for the three books on (175) recurrences and at a rate of (22%). Then the acting skill ranked second after it collected (82) recurrences at a rate of (10%). The other sub-skills came in varying degrees of interest from the textbook, while the skills of formulating questions and the skill of identifying main ideas were neglected. In light of this, the researcher recommended the need for balance in the percentages of including mental skills in the mathematics book for the second intermediate grade, and came up with a number of recommendations and suggestions.
Keywords: المهارات العقلية -- المناهج الدراسية -- العملية التعليمية -- طلبة المرحلة المتوسطة